EFFICACY OF KATI VASTI IN THE MANAGEMENT FOR BACK PAIN- CASE STUDY (International Journal of Ayurveda and Pharma Research, 2020)
Back pain is one of the most common symptoms and majority of people have back pain at least once in their life time. Excess weight, arthritis, osteoporosis, ligament strain, bulging of vertebral disk and urinary calculi are the more common causes for back pain. Vasti is an important treatment in the Ayurveda medicine especially for Vata diseases. Medicated liquids and oils are normally used for Vasti and it plays a key role in Panchakarma treatment. Narayana oil has an amazing power to control and eliminate Vata disorders. The present study was carried out in five male Subjects (between 30 to 70 years of age) who were attending to the District Ayurveda Hospital, Mullaitivu for the treatment of the back pain. This study was maintained on alternative days for 7 days until the period of 3 months Narayana oil was applied and slight massage for 5 minutes on the back, and put the black gram powder ring on the back then heated oil with equal to body temperature poured into that ring and left for 10 minutes. The consecutive visits, the subjects were all examined for the severity of the pain condition. Out of five, two subjects were completely relieved from back pain; two patients were relieved 90% of back pain and only one was relieved by 75%. Both Kati Vasti and Narayana oil are very effective to eliminate the Vata disorders. This study results stated that the Kati Vasti is very effective for the treatment of back pain.